Magnetoresistance enhancement in epitaxial magnetite films grown on vicinal substrates - SHVETS, IGOR; ARORA, SUNIL (My University, 2005)
The magnetoresistance MR behavior of epitaxial magnetite Fe3O4 grown on low-vicinal small miscut and high-vicinal large miscut MgO substrates is compared. Magnetization measurements on Fe3O4 films on high-vicinal substrates showed reduced magnetic moment as compared with the films grown on low-vicinal MgO, which correlates well with the expected reduction in magnetic moment due to step edge induced additional antiphase boundaries APBs with out-of-plane shift vectors. The MR is significantly higher 12.3% at 2 T for a 45 nm Fe3 O4 film on high-vicinal substrate than that observed 7.2% at 2 T for a film on low-vicinal substrate. A strong anisotropy in the MR is observed in correlation with the direction of atomic step edges. In addition to the increase in MR, the field dependency of the MR is also modified. The observed modification in the magnetotransport behavior of epitaxial Fe3O4 films is attributed to an enhanced spin scattering arising due to the presence of atomic height steps that lead to the formation of a greater density of antiferromagnetically coupled APBs.
PUBLISHED
Keywords: Surface Physics; thin films